Mechanical Calculation of Flexible Wires Taking into Account Taps to Electrical Apparatuses - Y. V. Bladyko; E. G. Ponomarenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
A method is proposed for the mechanical calculation of flexible wires of substation in the presence of one tap to an electrical apparatus located in the middle of the span, taking into account its real location. The technique takes into account the presence of tension insulators strings, different heights of the suspension of wires. The loads on the conductor and tap depend on the climatic regime and take into account wind and icy conditions, as well as temperature changes. The transition to another climatic regime is performed by solving the equation of state, taking into account the coefficients of the horizontal and vertical load of the given and initial regimes. Formulas are given for calculating load factors that take into account weight, wind and ice cover loads on wires and insulator strings, as well as the slope of the span. They are calculated for each climatic mode based on the actual location of the tap to the electrical apparatus and the forces from it to the busbar. It is shown that the calculation results are in good agreement with the proposed method and the computer program. Formulas are given for calculating the sag and horizontal deviations of the wires when the tap is located in the middle of the span. A method is proposed for calculating the components of the forces on the busbar from the tap, taking into account its real location in substation. Formulas for calculating these components are given for different variants of the tap orientation. Knowledge of the values of the components of concentrated forces from the tap allows to increase the accuracy of calculating the sag and tension of the substation wires. Formulas are given for calculating the coefficients of increasing the sag, taking into account the components of the forces from the tap.